EMPLOYEES AS SERVICE PROVIDERS: COMPENSATION ANALYSIS BASED ON EMPLOYMENT AGREEMENTS - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2025)
This study examines the relationship between the type of employment contract and the compensation received by employees as service providers, as well as the implications of such compensation on employee performance. The method used is a literature review with a normative legal approach, which analyses various literature, labour regulations, and previous research findings related to compensation and employment contracts. The findings indicate that compensation is significantly influenced by the type of employment contract, with employees under an Indefinite-Term Employment Contract (PKWTT) tending to receive more stable compensation and benefits compared to those under a Fixed-Term Employment Contract (PKWT). Fair and transparent compensation positively impacts motivation, loyalty, and the quality of services provided, thereby enhancing employee performance and the sustainability of service organisations. This study underscores the importance of aligning compensation practices with regulations and the dynamic needs of the workforce to foster employee well-being and corporate competitiveness.